PERTAMBANGAN GALIAN C DI KABUPATEN KAMPAR DALAM SENI LUKIS REALIS KONTEMPORER - MUHAMMAD AQIL AZIZI, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize environmental damage due to Galian C mining in the District XIII of Koto Kampar and Koto Kampar Hulu in Kampar District in contemporary realist painting. Displays Galactic mining activities that do not have operational permits and negative impacts on the surrounding environment. The method and process of work used in the creation of this painting works through several stages: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the Concept, (5) Completion. The results of the discussion are visualization of environmental damage that is increasingly damaged and has a negative impact on the environment as a result of Mining C in District XIII Koto Kampar and Koto Kampar Hulu Kampar District. As for the work discussed, it consists of ten contemporary realist paintings with the title: memakan badan jalan, tentang penambang batu, tambang untuk kehidupan #1,Tambang untuk kehidupan#2, Eksploitasi Alam #1, Eksploitasi Alam #2, Ekspoitasi Alam #3, Potret dampak negatif, Faktor X, Potret pascatambang.Kata kunci :Pertambangan, galian C, dampak, seni lukis.